2010
DOI: 10.1109/tnsre.2010.2047608
|View full text |Cite
|
Sign up to set email alerts
|

Sensor-Based Arm Skill Training in Chronic Stroke Patients: Results on Treatment Outcome, Patient Motivation, and System Usability

Abstract: As stroke incidence increases, therapists' time is under pressure. Technology-supported rehabilitation may offer new opportunities. The objective of this study was to evaluate patient motivation for and the feasibility and effects of a new technology-supported task-oriented arm training regime (T-TOAT). Nine chronic stroke patients performed T-TOAT (2 x 30 min/day, four days/week) during eight weeks. A system including movement tracking sensors, exercise board, and software-based toolkit was used for skill tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 55 publications
2
83
0
2
Order By: Relevance
“…24 Finally, a study investigating the perceived usability of a sensor-based training system for stroke patients showed that the system's usability was rated to be good at the end of the training session, but did not mention any user preferences. 31 In general we found that the methods used in the studies often lacked validation and standardization. Many studies had relative small number of participants and provided a limited amount of data.…”
Section: Discussionmentioning
confidence: 99%
“…24 Finally, a study investigating the perceived usability of a sensor-based training system for stroke patients showed that the system's usability was rated to be good at the end of the training session, but did not mention any user preferences. 31 In general we found that the methods used in the studies often lacked validation and standardization. Many studies had relative small number of participants and provided a limited amount of data.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known to which extent patients were motivated to comply with the prescribed exercise regimen and to which extent the training content on offer managed to keep them motivated. In a previous clinical trial where patients with stroke performed technology-supported, task-oriented arm training, 42 patients found that the exercises that were provided (n ¼ 22) were insufficient in number and in the challenge level to keep them motivated for prolonged training. Future research should focus on the identification of the number and variability of exercises that is needed to serve average patients' needs and to keep patients motivated for extensive exercise repetition and sufficient duration.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…For example, it has been utilized to evaluate technologies in the health care domain (e.g. evaluation of rehabilitation equipment for patients with stroke [9], robotics applied to rehabilitation [10], personal health records [11,12], prevention applications [13][14][15], tools to support diagnostic [16] or informal caregivers empowerment [17]), applications to browse the contents of maps [18] or videos [19], social networking sites [20], elearning environments [21,22], tools to support engineering work [23], virtual reality [15], remote labs management [24] or visualization of ontologies [25].…”
Section: Related Workmentioning
confidence: 99%